SEDIMENTOLOGY AND PALAEOENVIRONMENTAL RECONSTRUCTION OF AG-1 CORE OF AYVALIK REGION, NW TURKEY - Nikolaou, K.; Alysandratou, A.; Karanika, K.; Kaya, Y.; Inaner, H.; Christanis, K.; Iliopoulos, G.; Avramidis, P. (Bulletin of the Geological Society of Greece, 2016)
This study presents sedimentological and palaeontological data retrieved from a coastal lagoon near Ayvalik in NW Turkey. The objective of this study is to interpret the depositional environments and reconstruct the evolution of the study area during the late Holocene. 42 sediment samples have been retrieved from a 13m core. Sedimentological analyses such as grain size analysis, moment measures of mean, sorting, skewness and kurtosis, definition of total organic carbon (T.O.C.), total nitrogen (T.N.), colour and CaCO3 (%) were employed. Moreover, macro and microfossils were collected to reconstruct the depositional environments. The palaeoenvironmental - palaeoecological analyses indicated a closed shallow shelf environment (around 4000 to 2400 yr BP) that gradually turned into a leaky lagoon (around 2400 yr BP to present).